Impact of Vegetal Protein on the Physicochemical and Microstructural Properties of Microencapsulated Mexican Red Pitaya (Stenocereus thurberi) Juice - David Neder-Suárez; Carmen Oralia Meléndez-Pizarro; Esther Pérez-Carrillo; Jesús Alberto Vázquez-Rodríguez; María del Cielo Valdez-Cárdenas; Martha Graciela Ruiz-Gutiérrez; Carlos Abel Amaya-Guerra; Francisco Paraguay-Delgado; Armando Quintero-Ramos (AppliedChem)
The effects of different carrier agents—pea protein (PP), rice protein (RP), bean protein (BP), whey protein (WP), and maltodextrin (MT, as a control)—on pitaya juice encapsulation via spray drying were evaluated. Juice and carrier mixtures (30% w/v) were dried at 150 °C, and the resulting powders were analyzed for water activity (aw), hygroscopicity (Hg), water solubility (WSI), bulk density (BD), glass transition temperature (Tg), water absorption (WAI), antioxidant activity (AA), total polyphenol content (TPC), total betalain (TB) content, and TB stability. Vegetable proteins showed promising results, significantly impacting the protein content, Hg content, WAI, WSI, AA, TPC, and TB content and resulting in high Tg values. PP showed the best results, with high betalain retention (>30%), high TPC and AA, high protein levels, and low Hg, similarly to MT. WP had the highest TB, AA, and TPC but the lowest Tg (47.21 °C), thus reducing stability. Encapsulates obtained with plant protein-based wall materials presented high Tg (>58 °C); low aw, WSI, and Hg; high protein contents >40%; and adequate retention of bioactive compounds, with low degradation rate constants and long half-lives. Overall, plant proteins are promising alternatives to traditional carriers, offering improved stability and functionality in encapsulated products.